Is "socio-ecological culture" really being taken into account to manage conflicts in the coastal zone? Inputs from Spanish Mediterranean beaches. (December 2016) - Ariza, Eduard; Pons, Ferran; Breton, Françoise
Abstract: Legal instruments traditionally used for regulating beach management during the last decades have not been very effective in protecting beach socio-ecological systems in many countries. In the last 5 years, two new laws, which impact the Spanish Mediterranean coast, the Mediterranean ICZM Protocol and the amendment to the Ley de Costas 22/88 have been passed. This study analyzes the conflicts existing in various beaches on the Catalan coast and the potential of these new instruments to improve their management. The Protocol has better integrative potential and is more focused on governance than the LC. However, both show a limited capacity to influence beach management in the study sites due to various shortcomings: lack of specificity, lack of capacity to sanction, narrowness of the approach, lack of coordination with lower administrative levels, rigid institutional set up and an inability to restore coastal ecosystems. In order to improve management of some of the conflicts, we suggest scaling down and enforcing specific articles of the Protocol. Highlights: The new legal instruments have a limited capacity to manage beach conflicts. The ICZM Protocol has a better integrative potential. The ICZM Protocol lacks of specificity and capacity to sanction. The amendment of the LC 22/88 does not focus on governance.